Helminth parasites of freshwater fishes. X. On two new trematode parasites of freshwater fishes from Lucknow, India - Verma, Sneh Lata (Revista de Biología Tropical, 1973)
Two new species, Gomtia bagarii from the intestine of Bagarius yarrellii (Ham.) and Polyorchitrema rachai from the intestine of Eutropiichthys vacha (Ham.) from lhe river Gomati at Lucknow, India, are described. Keys to the specios of the genus Gomtia Thapar, 1930 and to the genus, Polyorchitrema Srivastava, 1939 are given.